TELOMERE LENGTH AND ATHEROSCLEROSIS - O. M. Drapkina; R. N. Shepel (Российский кардиологический журнал, 2016)
The development  and progression of atherosclerosis in most cases takes decades, and at early stages does not present clinically. Multiple studies results witness that telomere   length  reflects  total  grade   of  DNA damage by  the  factors  that  are responsible for atherosclerosis and its complications. Velocity of telomeres shortening  increases even before the disease onset  that may play diagnostic  and predictive role.